WRITING STRATEGIES APPLIED BY THE FOURTH SEMESTER STUDENTS IN THEIR ARGUMENTATIVE WRITING AT ENGLISH STUDY PROGRAM OF UNIROW TUBAN - Hefi Putri Noviasari; Ulfa Yuliasari; Christina Innocenti Panggabean (Universitas PGRI Ronggolawe Tuban, 2023)
This study is aimed to describe writing strategies applied by the fourth semester students of English language education program of PGRI Ronggolawe University Tuban in their argumentative writing. It includes 1) kinds of writing strategies applied by the students in their argumentative writing 2) the application of those kinds of strategies. This research used descriptive qualitative method. The subject of this research was five students who got the highest score in their previous writing subject. The researcher modified SILL questionnaires based on (Oxford, 1996) to observe their writing strategy, which covers six categorizes of strategies namely cognitive, metacognitive, memory, compensation, affective, and social strategy. The data from the questionnaire and the interview were analyzed descriptively. The result of this study indicated that all students applied all kinds of writing strategies. Compensation strategy became the most dominant strategy used by the students, followed by metacognitive strategy, memory strategy, cognitive strategy, affective strategy and social strategy. The students had different way to apply writing strategies. It depended on their condition and their needs while writing a text.